Prolongamento da vida pós-colheita de bananas-maçã submetidas ao 1-metilciclopropeno (1-MCP) – qualidade sensorial e física - Pinheiro, Ana Carla Marques (2009)
The objective of this work was to evaluate the effect of 1-methylcyclopropene (1-MCP) on the quality and extension of postharvest life of ‘Apple’ banana. The fruit, at degree 2 of peel color was treated with 50 nL.L–1 of 1-MCP for 0 (control), 6, 9, 12 and 24 hours. Next, It was stored at room temperature: 22 ± 2 °C 85 ± 5 per cent RH. The following sensory characteristics were evaluated: appearance of the fruit at degree 4 (greener than yellow) and degree 7 (yellow with brown spots) of peel color; peeling, aroma, flavor, firmness of pulp and global aspect of the fruit at degree 7, using a test of acceptability using the 9-point hedonic scale and also the intention of buying the fruit at degrees 4 and 7, using a 5-point scale. Also evaluated visually was the extension of postharvest life and instrumentally the peel color and pulp firmness. It was concluded that the application of 50 nL.L–1 for a period of 12 hours is the most suitable, because it promotes the extension of the postharvest life of `Apple` bananas, stored at room temperature for approximately 11 days, without affecting the sensory quality, buying intention, peel color and firmness of fruit when ripe, in comparison to control. Keywords: sensory analysis; Musa sp.; color; firmness; shelf life.